Retrospective review of spinal versus epidural anaesthesia for caesarean section in pre-eclamptic patients - Chiu, C.L.; Mansor, M.; Ng, K.P.; Chan, Y.K. (2003)
A 5-year retrospective survey of anaesthesia for caesarean section for mild/moderate and severe preeclampsia was performed, covering the period between 1 January 1996 and 31 December 2000. One hundred and twenty-one cases of non-labouring preeclamptic patients receiving spinal or epidural anaesthesia for caesarean section were included for analysis. Comparisons were made of the lowest blood pressures recorded before induction of anaesthesia, during the period from induction to delivery and the period from delivery to the end of operation. The decreases in blood pressure were similar after spinal and epidural anaesthesia. The use of intravenous fluids and ephedrine were also comparable in the two anaesthetic groups. There was no difference in maternal or neonatal outcome. Our result supports the use of spinal anaesthesia in preeclamptic women. Â© 2002 Elsevier Science Ltd. All rights reserved.